2001
DOI: 10.1590/s0103-31312001000100003
|View full text |Cite
|
Sign up to set email alerts
|

Actual and potential photosynthetic rates of tropical crop species

Abstract: The actual (A) and potential (Apot) photosynthetic rates of C3 and C4 tropical crop species grown under greenhouse conditions was compared. The following species were investigated: Oryza sativa, Phaseolus vulgaris, Glycine max, Helianthus annuus, Gossypium hirsutum, Manihot esculenta, Theobroma cacao, Coffea arabica, Hevea brasiliensis, and Eucalyptus urophylla × E. grandis, all from the C3 group, and Amaranthus sp., Panicum maximum, Pennisetum purpureum, Zea mays and Saccharum officinarum, from the C4 group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 15 publications
7
24
0
4
Order By: Relevance
“…The mean SLA was 130 cm 2 g -1 similar to those reported for Nacional Ecuadorian cacao grown in full sunlight in the region of Esmeraldas, Ecuador (Tezara et al, 2015) and lower than the SLA (170 and 239 cm 2 g -1 ) reported by Daymond et al, (2011) andDa Matta et al, (2001). However, more research in order to know the relationship between environmental conditions and SLA along the north and central of the Ecuadorian coast is necessary.…”
Section: Specific Leaf Areasupporting
confidence: 76%
“…The mean SLA was 130 cm 2 g -1 similar to those reported for Nacional Ecuadorian cacao grown in full sunlight in the region of Esmeraldas, Ecuador (Tezara et al, 2015) and lower than the SLA (170 and 239 cm 2 g -1 ) reported by Daymond et al, (2011) andDa Matta et al, (2001). However, more research in order to know the relationship between environmental conditions and SLA along the north and central of the Ecuadorian coast is necessary.…”
Section: Specific Leaf Areasupporting
confidence: 76%
“…Cacao seedlings show increasing rates of net photosynthesis (A) as the photosynthetically active radiation (PAR) increases to values in the range from near 400 (Joly, 1988) to 750 (Da Matta et al, 2001) µmol m -2 s -1 , corresponding to 20-30% of PAR at full sunlight, when SI is reached. About 95% of the maximum A is obtained with half SI.…”
Section: Effects Of Abiotic Factors On Growth and Development Of Cacamentioning
confidence: 99%
“…Plants generally have specific light needs, predominantly in the red and blue wavelengths (Messinger et al 2006). Under unfavorable light intensities in the vegetation canopy, plants are impelled to adapt because the balance in the red and far-red wavelengths is affected by shading, thereby influencing photosynthetic efficiency (Da Matta et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, plants occasionally do not show these variations or may even display distinct physiological behaviors based on light intensity (Da Matta et al 2001, Lima Jr. et al 2006. The phenotypic plasticity of a species and its interactions with abiotic factors in the environment could be associated with its response to light.…”
Section: Introductionmentioning
confidence: 99%